Analysis of the Effect of Product Quality and Service Quality on Repurchase Interest in Culinary UMKM Mediated by Mediating Customer Satisfaction: a Case Study on We'e Dewe Snacks - Yolanda Gilang Puspita (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to examine the effect of product quality and service quality on repurchase intention directly or indirectly through customer satisfaction. The variables studied were product quality (X1), service quality (X2), customer satisfaction (M), and repurchase intention (Y). The method used in this study is using quantitative approach and analyzed using SEM-PLS. Data collection was done by using a questionnaire which was distributed online using the google form. The population in this study are people who have bought Jajanan We'e Dewe products at least 1 (one) time. Meanwhile, the research sample criteria are the customers of Jajanan We'e Dewe who have visited IG, Whatsapp, or came directly to Jajanan We'e Dewe and have an interest or desire to repurchase Jajanan We'e Dewe products. The number of respondents in the study were 50 people. The result of the study had found that there was a significant influence on the effect of product quality and service quality on customer satisfaction, the effect of customer satisfaction on repurchase intention, and the effect of product quality and service quality on repurchase intention through customer satisfaction. Meanwhile, the direct effect on product quality and service quality on repurchase intention did not show significant results.